Linguagens sincréticas e construção da identidade na Revista Unesp Ciência: um estudo semiótico - Garrido, Bruno Sampaio [UNESP] (2015)
This research aims to analyse the general structure of meaning of Unesp Ciência magazine (UC) and, in the same way, the manner how the enunciator present in discourse of this magazine builds a simulacrum of itself (éthos) and of their readers (páthos), in order to producing a particular discursive style. The magazine, which has been edited by the communication department of São Paulo State University (Unesp) since September 2009, proposes to disclose the science made in/by the institution. Theoretical-methodological framework adopted in this research is based upon, mainly, on the discursive semiotics, proposed by Algirdas Julien Greimas and developed by his followers, in a dialogue with concepts brought from Philosophy of Science and Journalism theories. Through an analysis of syncretic languages on UC and enunciation marks which characterize the identity of the enunciation subject, we concluded this magazine imbricates elements which aggregate features of the news story genre and the scientific and institutional disclosure. In addition, visual narratives and setting of the enunciator éthos are decisive to creating a style which values an empathy to the enunciatee and a sensible experience with the utterance, creating effects of presenting and immersing. The institutional and militant character of discourse of UC also propels the name of Unesp and the responsible agents to correspondent scientific production, aggregating them an euphoric feature, and also specific values defended by institution - prominence, leadership, innovation, defence of the environment and of social demands (especially those related to minority groups)